Man and his environment - Singh,Indera P.(ed.); Tiwari , S.C.(ed.) (New Delhi, 1980)
The content of the present volume deals with such diverse problems as environmental hazards to which man is exposed, physique and body compositions, physical fitness , nutritional studies, man and biosphere , island and isolates and urban and rural populations in a variety of environmental settings and ecosystems.
Keywords: Environments